Policies for Building Post-conflict Peace. - Bigombe, B; Collier, P; Sambanis, N (2000)
Civil wars always end, but usually they restart. Globally, within the first ten years of the end of a conflict, 31% of them have resumed. African conflicts are even more prone to restart than the global average: half of African peace restorations last less than a decade. By applying theoretical frameworks to newly developed data sets of conflict, we find that the high incidence of peace collapse in Africa is not inevitable. To date, policies on the part of both the international community and post-conflict governments have been highly inefficient. Thus with better policies, the risk of peace collapse after African civil wars can be radically reduced. We outline some strategies that can assist war-to-peace transition in Africa.